دور الحكومة الإلكترونية في رفع كفاءة الخدمات الحكومية في ظل التحول الرقمي (دراسة حالة على خدمات وزارة الشباب والرياضة) / The Role of E-Government in Upgrading the Efficiency of Government Services in Light of Digital Transformation (Case Study of the Services of Ministry of Youth and Sport) - عبد التواب، عبد الناصر محمد على; مغيب، هبة صالح (معهد التخطيط القومى, 2026)
تهدف الدراسة إلى تحديد وتحليل وتعزيز دور الحكومة الإلكترونية في رفع كفاءة وتحسين الخدمات الحكومية، وتقييم مدى فعالية تطبيق الحكومة الإلكترونية في وزارة الشباب والرياضة، وتحليل التحديات والعقبات التي تواجه تنفيذ الحكومة الإلكترونية مع الاستفادة من التجارب الدولية الرائدة، بالإضافة إلى تقديم توصيات عملية لتعزيز دور الحكومة الإلكترونية ورفع كفاءة الخدمات الحكومية. وقد تحددت مشكلة الدراسة في تحديد وتقييم التأثير الفعلي للحكومة الإلكترونية في رفع كفاءة الخدمات الحكومية بوزارة الشباب والرياضة بجمهورية مصر العربية، حيث تنبع هذه المشكلة من عدة جوانب متكاملة تُظهر فجوة واضحة بين الطموحات الرقمية والواقع التنفيذي. اعتمدت الدراسة على المنهج الاستقرائي الاستنباطي باستخدام الأسلوب الوصفي التحليلي، الذي يقوم بتحليل البيانات والدراسات السابقة المتعلقة بالحكومة الإلكترونية والتحول الرقمي كما استخدمت الدراسة منهج دراسة الحالة، حيث تم تحليل واقع تطبيق الحكومة الإلكترونية في وزارة الشباب والرياضة. يتمثل مجتمع الدراسة في كافة العاملين بوزارة الشباب والرياضة بجمهورية مصر العربية، وتتكون عينة الدراسة من العاملين بوزارة الشباب والرياضة: تم اختيار 300 موظف من إجمالي 1300 موظف. وتم الاستعانة بالاستبيان كوسيلة بحث للكشف عن اراء عينة الدراسة كما تم اجراء المقابلات الشخصية مع قيادات الوزارة لدعم نتائج الاستبيان. وأظهرت النتائج أن تطبيق الحكومة الإلكترونية محرّك أساسي لرفع كفاءة الخدمات بوزارة الشباب والرياضة حيث تؤثر الحكومة الالكترونية بأبعادها المختلفة بنسبة 79.3% في كفاءة الخدمات الحكومية. وخلصت الدراسة الي عدة توصيات أبرزها انشاء منظومة عمل داخلية متكاملة وإنشاء منصة خدمات رقمية موحدة وتنفيذ برنامج تدريبي مخصص للعاملين وكذا رقمنة نظام الإشراف والرقابة على الهيئات الشبابية والرياضية وتبني استراتيجية "الحكومة الذكية" لتحقيق أقصى استفادة ممكنة من تطبيق الحكومة الالكترونية. The study aims to delineate, analyze, and enhance the role of E-government in optimizing public service efficiency. It further seeks to assess the efficacy of E-government implementation within the Ministry of Youth and Sports (MoYS), analyze the attendant challenges (drawing insights from leading international experiences), and provide practical recommendations. The research problem is centered on defining and quantifying the actual impact of E-government on enhancing government service efficiency at MoYS, stemming from a clear discrepancy between digital aspirations and operational reality. The study adopted the Deductive-Inductive approach utilizing the Descriptive-Analytical method, which involved analyzing extant data and prior studies related to E-government and digital transformation and a Case Study Approach to assess the reality of E-government application at the Ministry. The study's population comprised all MoYS employees, from which a sample of 300 employees was selected (out of a total of 1,300). A questionnaire was utilized as the primary research instrument, supplemented by personal interviews with Ministry leaders to corroborate the findings. The results revealed that E-government implementation acts as a primary catalyst for enhancing service efficiency at MoYS, with E-government dimensions collectively contributing 79.3% to the variance in government service efficiency. The study concluded with several key recommendations, most notably: establishing an integrated internal workflow system, creating a unified digital services platform, implementing a dedicated employee training program, digitizing the supervision and oversight system for youth and sports bodies, and adopting a "Smart Government" strategy to realize maximum potential benefit.